Organizational learning capability and organizational innovativeness: the mediating effect of transformational leadership style of academic managers / Shahri Abu Seman and Syed Jamal Abdul Nasir Syed Mohamad - Abu Seman, Shahri; Syed Mohamad, Syed Jamal Abdul Nasir (Universiti Teknologi MARA, Shah Alam, 2019)
The role of organizational learning in enhancing firm's innovativeness has become important to secure a sustainable competitive edge. This study attempts to explore this relationship by introducing a transformational leadership style as a mediator. The data were collected from 220 participants belonging to private higher education institutions in Malaysia through survey research using the structured interview schedule. The findings confirm organizational learning to be an important factor in promoting creativity in innovative organization. Transformational leadership Managers with learning ability improves their leadership skill and understanding to accumulate knowledge and experience to use it productively in challenging and competitive environment. This accumulated knowledge can further be utilized to enhance ability to anticipate the future and respond to customers' demands through products based on their innovation capability. The implications of the results for academics and practitioners are discussed.